In Vitro Probiotic Potential of Lactic Acid Bacteria Isolated from Aguamiel and Pulque and Antibacterial Activity Against Pathogens - Alicia Cervantes-Elizarrarás; Nelly del Socorro Cruz-Cansino; Esther Ramírez-Moreno; Vicente Vega-Sánchez; Norma Velázquez-Guadarrama; Quinatzin Yadira Zafra-Rojas; Javier Piloni-Martini (Applied Sciences, 2019)
Probiotics can act as a natural barrier against several pathogens, such Helicobacter pylori, a bacterium linked to stomach cancer. The aim of the present study was to isolate and identify lactic acid bacteria (LAB) from pulque and aguamiel, and evaluate their probiotic potential and antimicrobial effect on Escherichia coli, Staphylococcus aureus, and Helicobacter pylori. Ten isolates were selected and evaluated for in vitro resistance to antibiotics and gastrointestinal conditions, and antimicrobial activity against E. coli and S. aureus and the effect on H. pylori strains. 16S rRNA identification was performed. Ten potential probiotic isolates were confirmed as belonging to the genera Lactobacillus and Pediococcus. All the strains were susceptible to clinical antibiotics, except to vancomycin. Sixty percent of the isolates exhibited antimicrobial activity against E. coli and S. aureus. The growth of H. pylori ATCC 43504 was suppressed by all the LAB, and the urease activity from all the H. pylori strains was inhibited, which may decrease its chances for survival in the stomach. The results suggest that LAB isolated from pulque and aguamiel could be an option to establish a harmless relationship between the host and H. pylori, helping in their eradication therapy.